The Troubling Shortcomings of International Asset Freezes: The Hunt for Gaddafi's Lost Billions. Issue 4 (November 2021) - Pavlidis, Georgios
Abstract : Although international asset recovery is one of the key anti-corruption commitments under the United Nations Convention against Corruption and the African Union Convention on Preventing and Combating Corruption, a huge gap remains between commitments and implementation. The shortcomings of international asset freezes in the case of Libya, with billions of dollars unaccounted for, confirm this statement. In this article, I identify the major obstacles for recovering stolen assets in the case of Libya and I argue that the international community needs to enhance asset recovery and mutual legal assistance, as well as to explore bold ideas, such as the reversal of the burden of proof as to the illicit origin of the assets.